2007
DOI: 10.1111/j.1479-828x.2007.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of maternal age and episiotomy in the risk of anal sphincter tears during childbirth

Abstract: There are several independent risk factors that should be considered when making decisions regarding delivery mode. Maternal age and episiotomy in non-instrumental delivery are two of these.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 42 publications
3
7
0
2
Order By: Relevance
“…This is in agreement with the evidence that episiotomy decreases the risk of OASIS during instrumental delivery . Episiotomy is more protective when performed with instrumental versus spontaneous delivery …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with the evidence that episiotomy decreases the risk of OASIS during instrumental delivery . Episiotomy is more protective when performed with instrumental versus spontaneous delivery …”
Section: Discussionsupporting
confidence: 91%
“…23 Episiotomy is more protective when performed with instrumental versus spontaneous delivery. 24 In the present study, women delivering twins had a higher rate of instrumental deliveries, which is a well-recognized risk factor for OASIS. 25 However, the incidence of OASIS was conversely lower in this group.…”
Section: Discussionsupporting
confidence: 46%
“…The non-routine practice of episiotomies, among other recommendations, has been promoted within this care framework. Our assessment confirms, as found in other studies, that 1 st degree tears, considered benign lesions that do not require repair, are the most frequent occurrence in births where an episiotomy has not been performed [22][23][24] and that 2 nd degree tears are also more frequent among births without episiotomies, but the restrictive use of an episiotomy has prevented a greater proportion of women having had a surgical incision as opposed to a minor tear [25]. Finally, the study revealed how the restrictive use of episiotomies reduces their percentage without compromising the safety of women or newborns [26,27].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to a higher risk of anal sphincter damage in nulliparous women, we found a lower rate of episiotomy among nulliparous women who planned home birth [50]. The literature is inconclusive about the association between episiotomy and anal sphincter rupture [51, 52]. However, restrictive use of episiotomy has been recommended, as this is associated with less severe perineal damage [53].…”
Section: Discussionmentioning
confidence: 99%